Proposals to enhance thermal efficiency programs and air pollution control in south-central Chile - Schueftan, Alejandra (2015)
Major cities in South-central Chile suffer high levels of particulate matter PM10 and PM2.5 due to combustion of solid fuels for heating. Exposure to these air pollutants is recognized as a major contribution to ill health in the region. Here we discuss new strategies to reduce air pollution. Regulations and subsidies focusing on improved combustion by providing drier wood fuel and better stoves have been in effect since 2007. However, air pollution due to combustion of wood fuel has been steadily rising, along with reports on health consequences. The paper analyzes a survey of 2025 households in the city of Valdivia, which found that wood fuel quality, stove renewal, and awareness of programs are strongly affected by income level, and that higher consumption of wood fuel is found in households already having better stoves and drier wood fuel. The analysis suggests that regulations intended to improve combustion are influenced by user's behavior and have limited potential for lowering pollution. We conclude that thermal refurbishment has a larger potential for improvement, not yet been implemented as an energy policy for the majority. Here we propose improvements and additions to current programs to enhance effectiveness and cover the whole social spectrum.